Employees Empowerment and its Relationship to Competitive Advantage: A Case Study / Hotel Sector / Sultanate of Oman - Albahri, Khalaf Sulaiman (Journal of Economic, Administrative and Legal Sciences, 2024)
The study aimed to clarify the extent of the relationship between employee empowerment, which is represented in its dimensions (delegation of authority, training, motivation, work teams, and active participation) and competitive advantage, which is represented in its dimensions (cost leadership, focus, creativity) in the hotel sector in the Sultanate of Oman, in addition to identifying the differences. Statistics through the workers’ answers attributed to demographic variables, through testing the study hypotheses. To achieve the objectives of the study, the researcher followed the descriptive analytical approach, where he used the Social Statistical Package (SPSS.V_25) program to analyze the study data to suit the nature of the study in terms of its objectives and questions. The study population consists of workers in the hotel sector in the Sultanate of Oman, numbering five thousand two hundred and thirty employees distributed among several Six hundred and twelve hotel establishments in all categories in the Sultanate of Oman. A simple random sampling method was used. The sample amounted to three hundred and fifty-seven (357) working employees. The study also reached a set of results, the most important of which are: the existence of a positive relationship to employee empowerment, whose dimensions are represented by delegation of authority, training, motivation, work teams, and active participation in competitive advantage, and its combined dimensions of cost leadership, focus, and creativity. There are also no statistically significant differences. For the areas of employee empowerment, which is represented by the dimension of delegation of authority, in addition to the absence of statistically significant differences in the averages of the areas of employee empowerment due to the experience variable. The study recommended several recommendations, the most prominent of which are: paying attention to forming work teams and activating teamwork, developing an effective system of incentives, studying the factors of empowerment strategies, especially those related to training, in addition to identifying the obstacles that obstruct the process of implementing effective participation that encourages creativity and the creation of new ideas.
Keywords: employee empowerment; competitive advantage; hotel sector